Gaze alternation predicts inclusive next-speaker selection: evidence from eyetracking - Rühlemann, Christoph (Frontiers in Communication, 2024)
Next-speaker selection refers to the practices conversationalists rely on to designate who should speak next. Speakers have various methods available to them to select a next speaker. Certain actions, however, systematically co-select more than one particular participant to respond. These actions include asking 'open-floor' questions, which are addressed to more than one recipient and that more than one recipient are eligible to answer. Here, next-speaker selection is inclusive. How are these questions multimodally designed? How does their multimodal design differ from the design of 'closed-floor' questions, in which just one participant is selected as next speaker and where next-speaker selection is exclusive? Based on eyetracking data collected in naturalistic conversation and using a mixed-effects model, this paper demonstrates that unlike closedfloor questions, open-floor questions can be predicted based on the speaker's gaze alternation during the question. The discussion highlights cases of gaze alternation in open-floor questions and exhaustively explores deviant cases in closed-floor questions. It also addresses the functional relation of gaze alternation and gaze selection, arguing that the two selection techniques may collide, creating disorderly turntaking due to a fundamental change in participation framework from focally dyadic to inclusive. Data are in British and American English.